Detection and Measurement of Nuclear Radiations. (2017) - Priya, P.; Gowdami, J.; Roshini, V.; Sinthanai Selvi, G.
Abstract: Nuclear energy as we all know the main source of electricity in today's world. Though it's very important source of energy during unexpected situation leakage of nuclear radiation takes place. Hence the detection and constant measurement of nuclear radiations is very essential. But this requires human source for the monitoring which puts the life of human into risk. The aim of our project is to detect and measure the nuclear radiations with the help of sensors and transmit the readings to the officials over wireless communication.